Triangulating the implementation of hierarchical agglomerative clustering on MAR-learning usability data - Lim K.C.; Selamat A.; Mohamed Zabil M.H.; Yusoff Y.; Selamat M.H.; Alias R.A.; Puteh F.; Mohamed F.; Krejcar O. (IOS Press, 2023)
Augmented reality; Clustering algorithms; Machine learning; Usability engineering; English language teaching; Hierarchical agglomerative clustering; Mobile augmented reality; Performance metrics; Self-reported metrics; Usability; Hierarchical clustering